Why Does Emissions Trading under the EU ETS Not Affect Firms' Competitiveness? Empirical Findings from the Literature - Eugénie Joltreau; Katrin Sommerfeld (Institute of Labor Economics (IZA), 2017)
Environmental policies may have important consequences for firms' competitiveness or profit-ability. However, the empirical literature shows that hardly any statistically significant effects on firms can be detected for the European Union Emissions Trading Scheme (EU ETS). We explain why there are arguably no significant competitiveness effects on firms, at least not during the first two phases of the scheme (2005-2012). We also reason why the third phase (2013-2020) is likely to reveal similar results. We show that the main explanations for this finding are a large over-allocation of emissions allowances leading to a price drop and the ability of firms to pass costs onto consumers in some sectors. Cost pass-through combined with free allocation, in turn, partly generated windfall profits. In addition, the relatively low importance of energy costs indicated by their average share in the budgets of most manufacturing industries may limit the impact of the EU ETS. Finally, small but significant stimulating effects on innovation have been found so far.
Keywords: Q52; Q58; D22; 330; employment effects; firm-level competitiveness; environmental policies; EU ETS